FOOD INSECURITY AND COPING STRATEGIES AMONG RURAL FARMERS IN RINGIM LOCAL GOVERNMENT AREA OF JIGAWA STATE, NIGERIA - Kabara, A. M.; Rabi’u, I.; Ibrahim, U.; Adamu, H. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study aimed to analyze food security and coping strategies among rural farmers in Ringim Local Government Area of Jigawa State, Nigeria. The objectives of the study were to describe the socio-economic characteristics of the respondents, determine the food security status of rural farmers, determine factors influencing food security status among the rural farmers, identify coping strategies employed by the respondents, and identify food security constraints faced by the respondents. The study employed a three-stage random sampling technique in the selection of respondents. Data collected from primary sources were analyzed using descriptive statistics, logistic regression, and the food security index. Farm size, farm income, access to credit facilities, household size, were found to be significant determinants of food security status among rural farming households at 10%, 5%, 1% and 5% respectively. R-Square value was found to be 469, which means that 46.9% variation in the households’ food security status is explained by the variables captured in the model. Major coping strategies employed by the respondents include skipping meals (26.4%), reduction in quality and quantity of food consumed (17.9%), and sales of assets (19.3%). Major constraints faced by the rural farming households were inadequate supply of farm inputs (14.3%), pests and diseases (9.3%), and limited access to credit (7.1%). The study concluded that the majority of the rural farming households in the study area were food insecure. The study recommends that the government ensure an adequate and timely supply of farm inputs like seeds, chemicals, fertilizers, etc. It also recommends that the Government should ensure the control, eradication, and maintenance of good surveillance of the major economic pests and diseases whose outbreaks are responsible for large-scale damage/loss to agricultural production.